(untitled) (Contemporary Journal of Social Science Review, 2025)
Autism Spectrum Disorder (ASD) presents complex challenges for families, particularly in Pakistan where awareness, resources, and trained professionals remain limited. This qualitative study explores the lived experiences of ten parents raising children with ASD, using Colaizzi’s phenomenological method. Findings reveal emotional struggles, difficulty accessing diagnosis, financial burdens, social stigma, and coping strategies shaped by culture and religion. The study highlights the urgent need for policy reforms, parent support systems, and culturally contextualized interventions to improve the well-being of families living with ASD.